Characteristics of the complete mitochondrial genome of the monotypic genus Arctictis (Family: Viverridae) and its phylogenetic implications - Mitra,Siuli; Kunteepuram,Vaishnavi; Koepfli,Klaus-Peter; Mehra,Neha; Tabasum,Wajeeda; Sreenivas,Ara; Gaur,Ajay (PeerJ, 2019)
The binturong (Arctictis binturong) is classified as a member of the subfamily Paradoxurinae within the family Viverridae (Carnivora: Mammalia) and comprises nine subspecies spread across Southern and Southeast Asia. Here, we describe the complete mitochondrial genome of the Indian subspecies A. b. albifrons using next-generation sequencing methods. The total length of the A. b. albifrons mitogenome was 16,642 bp. Phylogenetic analyses based on 13 mitochondrial protein-coding genes placed the binturong as a sister taxon to Paguma larvata within the Paradoxurinae and supported the clustering of Genettinae and Viverrinae and the monophyly of Viverridae and six other families of feliforms, consistent with previous studies. Divergence time estimates suggest that the Viverridae diversified during the Miocene (22.62 Mya: 95% CI [20.78–24.54] Mya) and that Arctictis and Paguma split 12.57 Mya (95% CI [8.66–15.67] Mya). Further molecular studies are required to test the distinctiveness and diversity of the nine putative subspecies of binturong.
Keywords: Mitochondrial DNA; Time calibrated phylogeny; Arctictis binturong albifrons; Viverridae